CASELE TRADIŢIONALE DIN ŢARA MOŢILOR. FUNCŢIIE ŞI IMPACTUL LOR ASUPRA TURISMULUI (PANGEEA, 2025)
Populating upper basin Arieşului had an individual character and not community,current households taking born of seasonal houses. The starting point in building the houses is the archaic forme of houses built on distant to the village, in mountain,inhabited only during the cold period.